A Novel One‐Pot Synthesis of UV‐Blue ZnSe Nanocrystals in Aqueous Solution. Issue 3 (17th December 2012) - Fu, Shasha; Sun, Qizhuang; Li, Dingyun; Dong, Meiting; Liu, Shuxian; Huang, Chaobiao
Abstract Described herein is a novel one‐pot aqueous synthesis of ZnSe nanocrystals has featuring the utilization of Na2SeO3 and Zn(AC)2×2H2O as Se and Zn source, glutathione (GSH) as stabilizing agent and reducing agent. By this approach, the UV‐blue ZnSe QDs with quantum yield (QYs) up to 19% have been synthesized with a molar ratio of Se/Zn/GSH at 1:4:8.5 under aqueous conditions at 110 °C. XRD and TEM show the ZnSe QDs are zinc cubic structure particles with an average diameter of 3–5 nm.